TECHNOLOGY INFORMATION ADVANCE IN THE PUBLIC SECTOR - Pastor Carrasco, Carlos Alberto (2010)
The purpose of this paper it's analyze the work of government in the process of Modernization Management Systems, with emphasis on Information Technology, which is supported by the technological elements involved in the process and accounting professionals in organizations government, generating a profit to the Government Administration to achieve its objectives. In the public sector financial management, a factor negatively affecting its lack of reliable and timely information about progress and the final result of the economic and financial operations, to other factors, the large volume of transactions occurs daily and registration processes generated by its implementation. To overcome this problem the governments of Latin America, have been developing efforts to modernize financial management systems capable of generating timely, accurate, reliable and efficient as the result of the vital activities.